Teacher Training in Martial Arts and Combat Sports: Innovative Educational Models - Jonatas Duarte; Carlos Alexandre Fett (Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2025)
Martial arts and combat sports have grown significantly in recent decades, both in terms of the number of practitioners and scientific production, establishing themselves as relevant practices for health, athletic performance, and human development. In this scenario, the relevance of teacher training stands out, traditionally linked to the achievement of a black belt or equivalent, but marked by a technical character. Although effective in transmitting motor skills, this model neglects pedagogical and theoretical dimensions that are fundamental for critical and contextualized teaching. There are studies that demonstrate scientifically tested methods for teaching martial arts and combat sports. However, many teachers are unaware of these scientific advances with practical potential. Thus, this study proposes recommendations for teacher training in martial arts and combat sports, such as bringing science closer through theoretical-practical courses, lectures, and refresher programs; valuing master-apprentice guidance; and specializing in specific audiences. Such measures can contribute to professional qualification and the consolidation of more effective, safer teaching practices that are aligned with scientific evidence.